A polylactic acid composite material with shape memory properties and preparation method thereof
By adding polycaprolactone, modified graphene oxide and compatibilizer to polylactic acid, the problem of polylactic acid composite material retaining biodegradability while improving rigidity, toughness and shape memory performance is solved, and the comprehensive performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202111325698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-11-10
AI Technical Summary
The prior art is difficult to effectively improve the rigidity, toughness and shape memory properties of polylactic acid blends while retaining biodegradability.
Polycaprolactone, modified graphene oxide and compatibilizer are added to polylactic acid. Through the flexibility and biodegradability of polycaprolactone, the stereocrystal formation ability of modified graphene oxide, and the interface compatibility improvement of the compatibilizer, the comprehensive performance of composite materials is improved.
It significantly improves the toughness, rigidity and shape memory performance of polylactic acid composite materials, while retaining biodegradability, achieving the improvement of the overall performance of the material.
Smart Images

Figure BDA0003347024260000031 
Figure BDA0003347024260000032 
Figure BDA0003347024260000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer material processing, and in particular relates to a polylactic acid composite material with shape memory performance and a preparation method thereof. Background Art
[0002] Shape memory polymers (SMPs) are a type of smart polymer material that can respond to external stimuli (such as temperature, force, electromagnetism, solvents, etc.), change from an initial shape to a temporary shape, and finally return to the initial shape. Compared with traditional shape memory alloys, SMPs have the characteristics of light weight, large deformation, strong plasticity, and low manufacturing cost. They have broad application prospects in the fields of medical care, electronic communications, aerospace, etc. Therefore, the preparation, structure and performance regulation, and mechanism research of high-performance SMPs have become one of the important topics in current polymer science research.
[0003] Polylactic acid (PLA) is biogenic, biodegradable and biocompatible. When used in tissue engineering and medical fields such as artificial muscles, artificial joints and surgical sutures, it needs to show a good shape memory effect. As a semi-crystalline polymer, PLA has a certain shape memory ability and shows a high shape fixation rate. However, its inherent brittleness greatly limits the shape memory property, and it is prone to brittle fracture when stretched at room temperature. In addition, PLA usually crystallizes slowly, has a low degree of crystallinity, and has a low content of crystalline regions as physical crosslinking points. At the same time, the molecular chain is rigid and the amorphous region has weak mobility, resulting in a low shape recovery rate. Therefore, it is of great scientific value and practical significance to adopt an effective method to construct the microstructure of the PLA system and improve its shape memory performance.
[0004] Polycaprolactone (PCL) is a fully biodegradable aliphatic polyester with a relatively flexible molecular chain and excellent toughness. Graphene is a carbon-based rigid nanoparticle that has developed rapidly in recent years. It has low density, large specific surface area, excellent mechanical, thermal and electrical properties, and has been rapidly developed in the field of polymer composites. In order to improve the interaction between graphene and polymers and improve its dispersibility, its surface is usually modified and functionalized. For example, the surface of graphene can be oxidized to obtain graphene oxide (GO) with polar groups such as -OH, -O-, and -COOH on the surface. It is difficult to achieve a balance of rigidity and toughness and good shape memory properties of polylactic acid materials by adding a single component to PLA. By adding suitable types of polymers and inorganic particles at the same time, a multi-component biodegradable polylactic acid-based composite material can be prepared to achieve complementary advantages between different components, effectively improve its brittleness while ensuring strength, achieve a balance of rigidity and toughness, and have good shape memory properties. However, the existing technology is still unable to effectively improve the comprehensive properties of polylactic acid blends such as rigidity, toughness and shape memory while retaining biodegradability.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a polylactic acid composite material with shape memory properties. By simultaneously adding polycaprolactone, modified graphene oxide and a compatibilizer to polylactic acid, the comprehensive properties of the polylactic acid composite material such as rigidity, toughness and shape memory are effectively improved while retaining biodegradability.
[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is: a polylactic acid composite material with shape memory performance, comprising the following components:
[0008] Polylactic acid, polycaprolactone, modified graphene oxide, compatibilizer.
[0009] In the above scheme, by adding polycaprolactone to polylactic acid and utilizing the excellent biodegradability, good flexibility, high elongation at break and other characteristics of polycaprolactone, the toughness and shape memory properties of the polylactic acid composite material are greatly improved.
[0010] By adding a compatibilizer, the compatibility and interaction between polylactic acid and polycaprolactone are greatly improved, and the strength and shape memory properties of the polylactic acid composite material are further improved.
[0011] Furthermore, the mass percentage of each component in the composite material is:
[0012]
[0013] Furthermore, the mass percentage of each component in the composite material is:
[0014]
[0015] Furthermore, the modified graphene oxide is graphene oxide with dextrorotatory lactic acid grafted on the surface.
[0016] Furthermore, the polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and the content of D-lactic acid is less than 6%.
[0017] Preferably, the content of dextrorotatory lactic acid is less than 4%.
[0018] In the above scheme, the content of dextrorotatory lactic acid in polylactic acid is relatively small, that is, the content of l-lactic acid is relatively large, which facilitates the formation of stereocrystals between the l-lactic acid in polylactic acid and the dextrorotatory lactic acid in modified graphene oxide during the preparation of the composite material, providing more physical cross-linking points for the composite material system.
[0019] Furthermore, the compatibilizer includes one or more of Joncryl ADR, diisocyanate, polyisocyanate, maleic anhydride, and succinic anhydride.
[0020] In the above schemes, the compatibilizers all have reactive active groups that can react with the polylactic acid matrix to improve the interfacial compatibility of polylactic acid, thereby greatly improving the compatibility and interaction between polylactic acid and polycaprolactone.
[0021] Furthermore, the weight average molecular weight of the polylactic acid is 100,000 to 300,000, and the weight average molecular weight of the polycaprolactone is 50,000 to 200,000.
[0022] Furthermore, the composite material has a tensile strength of 65 to 72 MPa, an elongation at break of 250 to 450%, a shape memory fixation rate of 92 to 98%, and a shape recovery rate of 82 to 90%.
[0023] A method for preparing a polylactic acid composite material with shape memory performance comprises: uniformly mixing polylactic acid, polycaprolactone, modified graphene oxide and a compatibilizer according to mass percentage, and preparing the composite material through melt blending and extrusion.
[0024] In the above scheme, polylactic acid, polycaprolactone, modified graphene oxide, and a compatibilizer can be melt-blended by a twin-screw extruder or an internal mixer, so that polycaprolactone and modified graphene oxide can be uniformly dispersed in the polylactic acid matrix with an ideal phase domain size, and the rigidity, toughness, and shape memory properties of the resulting polylactic acid composite material are significantly improved.
[0025] The polylactic acid composite material can also be directly produced by extrusion molding, blow molding, injection molding and the like.
[0026] Furthermore, the temperature of the melt blending is 180-200°C.
[0027] In the above scheme, the preparation method of the modified graphene oxide comprises the following steps:
[0028] (1) adding graphene oxide, 1,4-butanediol, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to an N,N-dimethylformamide solvent, stirring at room temperature, and obtaining graphene oxide with 1,4-butanediol grafted on the surface after centrifugal separation and vacuum drying;
[0029] (2) A certain amount of dextrorotatory lactic acid, graphene oxide with 1,4-butanediol grafted on the surface, stannous isooctanoate and solvent toluene are added into a flask, and a homogeneous solution is formed by ultrasonic treatment. Then, the solution is stirred, separated, washed and dried to obtain graphene oxide with dextrorotatory lactic acid grafted on the surface.
[0030] The dextrorotatory lactic acid grafted on the surface of graphene oxide can form stereocrystals with the l-lactic acid in polylactic acid, thereby acting as a physical cross-linking point, improving the compatibility of modified graphene oxide and polylactic acid, and at the same time improving its shape memory properties.
[0031] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0032] 1. The present invention modifies polylactic acid with biodegradable polycaprolactone, which not only effectively improves the toughness of polylactic acid but also retains its biodegradability.
[0033] 2. The present invention improves the dispersibility of graphene oxide in the polylactic acid matrix by adding right-lactic acid-modified graphene oxide, and can also form stereocrystals with the polylactic acid matrix, providing physical crosslinking points for the composite material system, thereby improving the rigidity and shape memory properties of the composite material.
[0034] 3. The present invention also adds a compatibilizer, which greatly improves the compatibility and interaction between polylactic acid and polycaprolactone, as well as the rigidity of the composite material.
[0035] The present invention provides a polylactic acid composite material with shape memory performance. Modified graphene oxide and biodegradable polycaprolactone are added as modifiers of polylactic acid, and stereocrystals are formed by the right-handed lactic acid on the surface of the modified graphene oxide and the left-handed lactic acid of the polylactic acid, so as to serve as physical crosslinking points of the composite material system. The use of a compatibilizer greatly improves the interfacial compatibility and interaction between polylactic acid and polycaprolactone. By reasonably optimizing the ratio of each component and giving full play to its role, the toughness, rigidity and shape memory performance of the polylactic acid composite material are effectively and synchronously regulated. The preparation method provided by the present invention is simple and easy to implement, and has a wider application. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is clearly and completely described below in conjunction with some embodiments. It can be understood by those skilled in the art that the following implementation is only used to explain the technical principle of the present invention and is not intended to limit the scope of protection of the present invention. For example, although the present invention describes the various steps of the method of the present invention in a specific order, these orders are not restrictive. Without departing from the basic principles of the present invention, those skilled in the art can perform the steps in different orders.
[0037] The shape memory properties of the prepared polylactic acid composite material are tested according to the following test method: the long block sample is immersed in a 70°C constant temperature water bath and kept for 2 minutes, and the sample is bent into an "L" shape (θ1 = 90°) under the action of an external force. While maintaining the external force, the "L"-shaped sample is transferred to a 0°C constant temperature water bath and kept for 2 minutes. The external force is removed, and the "L"-shaped sample will recover to a certain angle, and the bending angle is θ2 at this time. The sample is completely immersed in a 70°C constant temperature water bath again, and the "L"-shaped sample recovers to its original shape. The remaining bending angle that is not completely recovered to the original shape is θ3. The shape memory fixation rate R of the material f and the response rate R r Calculate according to formula 1 and 2 respectively:
[0038] R f =θ2 / θ1 (1)
[0039] R r =(θ2-θ3) / θ2 (2)
[0040] Each sample was tested 5 times and the average value was taken.
[0041] The tensile strength and elongation at break of the composite materials were measured in accordance with the national standard GB / T 1040.2-2006.
[0042] Example 1
[0043] 2 g of GO and 5 g of 1,4-butanediol (BD) were added to 100 ml of N,N-dimethylformamide solvent, and 0.02 g of dicyclohexylcarbodiimide and 0.02 g of 4-dimethylaminopyridine as reaction catalysts were added at room temperature, stirred for 12 hours, and the graphene oxide GO-g-BD with 1,4-butanediol grafted on the surface was obtained after centrifugal separation and vacuum drying; 20 g of dextrorotatory lactic acid (D-LA), 0.2 g of GO-g-BD, 0.1 ml of stannous isooctanoate (Sn(Oct)2) and 250 ml of toluene were added to a flask, and a homogeneous solution was formed by ultrasonic treatment for 20 minutes, and then stirred at 120°C for 3 days. After separation, washing and drying, the graphene oxide GO-g-PDLA with dextrorotatory lactic acid grafted on the surface was obtained.
[0044] 86wt% of PLA with a weight average molecular weight of 100,000, 11wt% of PCL with a weight average molecular weight of 50,000, 2wt% of modified graphene oxide and 1wt% of Joncryl ADR4368 are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 2%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0045] Example 2
[0046] The preparation of modified graphene oxide GO-g-PDLA is the same as that in Example 1.
[0047] 54.1wt% of PLA with a weight average molecular weight of 300,000, 45wt% of PCL with a weight average molecular weight of 200,000, 0.6wt% of modified graphene oxide, and 0.3wt% of Joncryl ADR4368 are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 2%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0048] Example 3
[0049] The preparation of modified graphene oxide GO-g-PDLA is the same as that in Example 1.
[0050] 50wt% of PLA with a weight average molecular weight of 100,000, 44wt% of PCL with a weight average molecular weight of 50,000, 3wt% of modified graphene oxide and 3wt% of diisocyanate are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 5%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0051] Example 4
[0052] The preparation of modified graphene oxide GO-g-PDLA is the same as that in Example 1.
[0053] 89.8wt% of PLA with a weight average molecular weight of 300,000, 10wt% of PCL with a weight average molecular weight of 200,000, 0.1wt% of modified graphene oxide, and 0.1wt% of polyisocyanate are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 5%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0054] Comparative Example 1
[0055] The preparation of modified graphene oxide GO-g-PDLA is the same as that in Example 1.
[0056] 87wt% of PLA with a weight average molecular weight of 100,000, 11wt% of PCL with a weight average molecular weight of 50,000 and 2wt% of modified graphene oxide are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 2%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0057] Comparative Example 2
[0058] 89wt% of PLA with a weight average molecular weight of 100,000 and 11wt% of PCL with a weight average molecular weight of 50,000 are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 2%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0059] Comparative Example 3
[0060] The preparation of modified graphene oxide GO-g-PDLA is the same as that in Example 1.
[0061] 98wt% of PLA with a weight average molecular weight of 100,000 and 2wt% of modified graphene oxide are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 2%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0062] Comparative Example 4
[0063] 86wt% of PLA with a weight average molecular weight of 100,000, 11wt% of PCL with a weight average molecular weight of 50,000, 2wt% of pure graphene oxide and 1wt% of Joncryl ADR4368 are uniformly mixed to obtain a mixture, wherein the D-LA content in the PLA is 2%, and then the mixture is melt-blended at a temperature of 180-200°C using a twin-screw extruder to obtain a polylactic acid composite material through extrusion.
[0064] Experimental example
[0065] Referring to the implementation scheme of Example 1, the contents of the components in the composite material and the preparation conditions were changed to obtain Examples 1 to 4; the components and the contents of the components in the composite material were changed to obtain Comparative Examples 1 to 4.
[0066] This experimental example tests the composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4, and the test results are shown in Table 1:
[0067] Table 1: Physical and chemical properties of composite materials
[0068]
[0069]
[0070] It can be seen from the above test results that the mass percentage content and preparation conditions of each component in the composite materials in Examples 1 to 4 are within the specified range of the present invention, and the physical and chemical properties of the prepared composite materials are relatively excellent; because the mass percentage content and preparation conditions of each component in the composite materials in Examples 1 and 2 are within the preferred range of the specified range, the physical and chemical properties of the prepared composite materials are better than those of Examples 3 and 4.
[0071] The components of the composite material in Comparative Example 1 do not use a compatibilizer relative to Example 1, so the physical and chemical properties of the composite material are reduced because the compatibility of PLA and PCL is poor without the effect of a compatibilizer, which affects its mechanical properties. The components of the composite material in Comparative Example 2 do not use modified graphene oxide relative to Comparative Example 1, so the physical and chemical properties of the composite material are reduced because the polylactic acid system cannot form stereocrystals without the use of modified graphene oxide, which leads to fewer physical crosslinking points, affecting the mechanical properties and shape memory properties of the composite material. The components of the composite material in Comparative Example 3 do not use polycaprolactone relative to Comparative Example 1, which reduces the elongation at break of the composite material, thereby reducing the physical and chemical properties of the composite material. The components of the composite material in Comparative Example 4 are relative to those in Example 1, except that the modified graphene oxide is replaced by pure graphene oxide. Since the surface of pure graphene oxide is not grafted with dextrorotatory lactic acid, it cannot form stereocrystals with the l-lactic acid in polylactic acid, cannot serve as physical cross-linking points, and has poor compatibility with the matrix, resulting in reduced physical and chemical properties of the composite material.
[0072] It can be seen from the above results that only when polycaprolactone, modified graphene oxide and compatibilizer are added to polylactic acid at the same time, and the mass percentage content and preparation conditions of each component are within the specified range of the present invention, the physical and chemical properties of the prepared composite material are relatively excellent, and the comprehensive properties of the polylactic acid composite material such as rigidity, toughness and shape memory are effectively improved while retaining its biodegradability.
[0073] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A polylactic acid composite material with shape memory properties, characterized in that: Includes the following components: The modified graphene oxide is graphene oxide with dextrorotatory lactic acid grafted on the surface; The polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and the content of the D-lactic acid is less than 6%.
2. The polylactic acid composite material with shape memory properties according to claim 1, characterized in that: The mass percentage of each component in the composite material is:
3. The polylactic acid composite material with shape memory properties according to claim 1, characterized in that: The content of dextrorotatory lactic acid in the polylactic acid is less than 4%.
4. A polylactic acid composite material with shape memory properties according to any one of claims 1 to 3, characterized in that: The compatibilizer includes one or more of Joncryl ADR, polyisocyanate, maleic anhydride and succinic anhydride.
5. The polylactic acid composite material with shape memory properties according to claim 4, characterized in that: The polyisocyanate includes diisocyanate.
6. A polylactic acid composite material with shape memory properties according to any one of claims 1 to 3, characterized in that: The weight average molecular weight of the polylactic acid is 100,000 to 300,000, and the weight average molecular weight of the polycaprolactone is 50,000 to 200,000.
7. A polylactic acid composite material with shape memory properties according to any one of claims 1 to 3, characterized in that: The composite material has a tensile strength of 65 to 72 MPa, an elongation at break of 250 to 450%, a shape memory fixation rate of 92 to 98%, and a shape recovery rate of 82 to 90%.
8. A method for preparing a polylactic acid composite material with shape memory properties according to any one of claims 1 to 7, characterized in that: include: After polylactic acid, polycaprolactone, modified graphene oxide and a compatibilizer are uniformly mixed according to the mass percentage, a composite material is prepared through melt blending and extrusion.
9. The method for preparing a polylactic acid composite material with shape memory properties according to claim 8, characterized in that: The temperature of the melt blending is 180-200°C.
Citation Information
Patent Citations
Modified polylactic acid / polycaprolactone composite material and preparation method thereof
CN102643523A
Self-repair material and article with shape memory effect and preparation method thereof
CN106633721A